Ants as a Character Learning Media from a Qur'an and Hadith Perspective - Asyabaabudzaki, Asyabaabudzaki; Azhar, Muhammad (Institut Agama Islam Negeri (IAIN) Curup, 2023)
A teaching and learning activity does not only require the right method, but also requires interesting learning media so that later the learning process becomes interesting and the learning objectives can be achieved properly. Learning media is any object that can be felt and seen by students. One of the learning media that is so close to human daily life is ants. Small animal whose name has been immortalized by Allah in the Koran. In this case, of course, the author wants to reveal that ants can be used as a character learning medium. Which this article was written based on a study that the authors found through a hermeneutical approach with the nature of library research. The analysis that the writer uses in this study is the analysis of the text and the meaning contained in the reading that the writer uses, in which case the writer uses texts from the Koran and hadith. Based on the research conducted by the authors, the authors found that ants are animals that have religious, unselfish, and honest characteristics. This of course can be used in instilling character and morals in students.